Characterization of the complete mitochondrial genome of Lepus comus, the endemic Lepus in China - Jing Huang; Wang Lin; Dandan Wu; Lifeng Cai; Xiumei Wang; Jianhui Huang (Mitochondrial DNA. Part B. Resources, 2019)
Lepus comus is the endemic species in China and has been listed on the IUCN Red List in 2013. In this study, we undertook and obtained the complete Lepus comus mitochondrial genome. The circular mitochondrial genome sequence is 17,534 bp in size, containing 13 protein-coding genes (PCGs), 21 transfer RNA (tRNA) genes, 2 ribosome RNA (rRNA) genes and a longer D-loop region of 2,610 bp in length. The base composition of the mtDNA is as follows: 31.5% of A, 29.8% of T, 29.8% of C and 13.3% of G, with a total G + C content of the mtDNA 38.7% and A + T of 61.3%. The phylogenetic Maximum-Likelihood (ML) tree was constructed to validate the taxonomic status of Lepus comus, exhibiting the closest relationship with Lepus tibetanus. The study of the complete Lepus comus mitochondrial genome can provide a reference taxonomic relationships and more basic data for future.